Butterflies embrace maladaptation and raise fitness in colonizing novel host. (26th February 2019) - Singer, Michael C.; Parmesan, Camille
Abstract: We illustrate an evolutionary host shift driven by increased fitness on a novel host, despite maladaptation to it in six separate host‐adaptive traits. Here, local adaptation is defined as possession of traits that provide advantage in specific environmental contexts; thus individuals can have higher fitness in benign environments to which they are maladapted than in demanding environments to which they are well adapted. A population of the butterfly Euphydryas editha adapted to a long‐lived, chemically well‐defended host, Pedicularis, had traditionally been under natural selection to avoid the ephemeral, less‐defended Collinsia . The lifespan of Collinsia was so short that it senesced before larvae entered diapause. After logging killed Pedicularis in clear‐cut patches and controlled burning simultaneously extended Collinsia lifespan, insect fitness on Collinsia in clearings suddenly became higher than on Pedicularis in adjacent unlogged patches. Collinsia was rapidly colonized and preference for it evolved, but insects feeding on it retained adaptations to Pedicularis in alighting bias, two aspects of postalighting oviposition preference, dispersal bias, geotaxis, and clutch size, all acting as maladaptations to Collinsia . Nonetheless, populations boomed on Collinsia in clearings, creating sources that fed pseudosinks in unlogged patches where Pedicularis was still used. After c. 20 years, butterfly populations in clearings disappeared and the metapopulation reverted to Pedicularis ‐feeding. Here we show, via experimental manipulation of oviposition by local Pedicularis ‐adapted and imported Collinsia ‐adapted butterflies, that the highest survival at that time would have been from eggs laid in clearings by butterflies adapted to Collinsia . Second highest were locals on Pedicularis . In third place would have been locals on Collinsia in clearings, because local females maladaptively preferred senescent plants. Collinsia had been colonized despite maladaptation and, after successional changes, abandoned because of it. However, the abandoned Collinsia could still have provided the highest fitness, given appropriate adaptation. The butterflies had tumbled down an adaptive peak.